2002
DOI: 10.1080/09687680210166226
|View full text |Cite
|
Sign up to set email alerts
|

Lipid matters: nicotinic acetylcholine receptor-lipid interactions (Review)

Abstract: Ligand-gated ion channels mediate fast intercellular communication in response to endogenous neurotransmitters. The nicotinic acetylcholine receptor (AChR) is the archetype molecule in the superfamily of these membrane proteins. Early electron spin resonance studies led to the discovery of a lipid fraction in direct contact with the AChR, with rotational dynamics 50-fold slower than those of the bulk lipids. This AChR-vicinal lipid region has since been postulated to be a possible site of lipid modulation of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 54 publications
1
34
0
Order By: Relevance
“…In general, as cholesterol resides in the plasma membrane, it is logical to expect that it is the TM domains that are critical for the sensitivity of the channels to cholesterol. Indeed, 2 current models of cholesterol-ion channel interactions, a lipid belt model (10,11) and a hydrophobic mismatch model (12,13), both focus on the interactions of cholesterol, directly or indirectly, with the TM domains of the channels. In the lipid belt model, it is proposed that channels interact directly with the boundary lipids surrounding the TM domains (10,11), and in the hydrophobic mismatch model, it is proposed that the hydrophobic mismatch between the TM domains and the lipid core of the membrane determines the energy required to change the conformation state of the channels from closed to open (12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, as cholesterol resides in the plasma membrane, it is logical to expect that it is the TM domains that are critical for the sensitivity of the channels to cholesterol. Indeed, 2 current models of cholesterol-ion channel interactions, a lipid belt model (10,11) and a hydrophobic mismatch model (12,13), both focus on the interactions of cholesterol, directly or indirectly, with the TM domains of the channels. In the lipid belt model, it is proposed that channels interact directly with the boundary lipids surrounding the TM domains (10,11), and in the hydrophobic mismatch model, it is proposed that the hydrophobic mismatch between the TM domains and the lipid core of the membrane determines the energy required to change the conformation state of the channels from closed to open (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, epithelial Na ϩ channels and TrpC channels were shown to be inhibited by cholesterol depletion (8,9). In general, 3 basic mechanisms have been proposed: (i) specific interaction of a channel protein with cholesterol as a boundary lipid (10,11), (ii) hydrophobic mismatch between the channel and the lipid core of the membrane (12,13), and (iii) indirect effects through the interactions of ion channels with regulatory lipids or proteins within the environment of cholesterol-rich membrane domains (1,14,15). The structural basis of the sensitivity of ion channels to cholesterol, however, is unknown.…”
mentioning
confidence: 99%
“…62). Delipidation studies of nAChR indicated that a lipid/protein mole ratio below ϳ45 causes irreversible inactivation of the receptor, consistent with the requirement of an annular shell of lipids around the periphery of the hydrophobic region (63).…”
Section: Effects Of the Bilayer On Receptor Structure And Functionmentioning
confidence: 99%
“…However, it is to be noted that these interactions are not conserved across the family (21). The strategic location of the ECD-TMD interface also makes this region a likely target for lipid-mediated effects on channel function (22)(23)(24). Interestingly, sequence analysis predicts the presence of a potential cholesterol-binding motif in GLIC at the pre-M1 region of the interface (25).…”
mentioning
confidence: 99%